Kredit Bermasalah dan Likuiditas: Dampak Terhadap Profitabilitas Bank Cabang Jatitujuh Perumda BPR Majalengka - Anan, Ibad Badrul; Hasanah, Ade Sobariah; Tajrani, Dini Tiara (Papanda Publisher, 2024)
This research aims to determine the development and influence of Problem Loans and Liquidity on Profitability at Perumda BPR Jatitujuh Branch, Majalengka Regency. This research uses descriptive methods and verification research methods with a quantitative approach. The data used in this research is secondary data in the form of financial reports of Perumda BPR Jatitujuh Branch, Majalengka Regency for 2016-2020 which were obtained directly through interviews. The number of samples in this research was 5, namely 5 years of financial reports obtained using purposive sampling techniques. Data analysis in this research uses multiple regression analysis with the help of the IBM SPSS Statistics version 25 application. The research results show that partially non-performing loans have a negative and significant effect on profitability levels and liquidity has a positive and significant effect on profitability. Simultaneously, non-performing loans and liquidity have a positive and significant effect on profitability at Perumda BPR Jatitujuh Branch, Majalengka Regency for the 2016-2020 period. It would be better for Perumda BPR Jatitujuh Branch to pay attention to the criteria for prospective customers and handle problem loans carefully so that the credit being handled runs smoothly and there are no bad debts, as well as paying attention to the quality of credit distributed to avoid problem loans so as to obtain profits or income from credit. which was distributed amidst tightening liquidity ratios.